1993
DOI: 10.1080/09553009314551291
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective Effects of Cimetidine in Mouse Bone Marrow Cells Exposed to γ-rays as Assayed by the Micronucleus Test

Abstract: An in vivo micronucleus assay using mouse bone marrow for identifying the radioprotective effect of cimetidine is described. The influence of cimetidine, an antagonist to the histamine H2 receptor, on the kinetics of radiation-induced micronuclei was tested in the CD-1 male mouse. Cimetidine was administered at 15 mg/kg i.p. 2 h prior to irradiation of mouse given various doses of gamma-rays from 0.25 to 1 Gy. The frequency of micronucleated polychromatic erythrocytes (PCEs) and normochromatic erythrocytes (NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The majority of MN present in cells following high-dose radiation exposure are extra-nuclear DNA fragments arising from acentric chromosome fragments originating from unrepaired or misrepaired DSBs [ 58 ]. Previous studies examining the dose–response relationship for γ and X-ray exposures and mouse bone marrow MN-PCE support a linear or linear-quadratic function for exposures to low to moderate doses of ionizing radiation (e.g., 0.1 to 0.5 Gy) [ 54 , 56 , 59 , 60 , 61 , 62 , 63 ]. More damaging radiations (>1 Gy) have been shown to prolong the erythroblast cell cycle and delay the temporal appearance of radiation-induced MN-PCE in the bone marrow [ 53 , 54 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of MN present in cells following high-dose radiation exposure are extra-nuclear DNA fragments arising from acentric chromosome fragments originating from unrepaired or misrepaired DSBs [ 58 ]. Previous studies examining the dose–response relationship for γ and X-ray exposures and mouse bone marrow MN-PCE support a linear or linear-quadratic function for exposures to low to moderate doses of ionizing radiation (e.g., 0.1 to 0.5 Gy) [ 54 , 56 , 59 , 60 , 61 , 62 , 63 ]. More damaging radiations (>1 Gy) have been shown to prolong the erythroblast cell cycle and delay the temporal appearance of radiation-induced MN-PCE in the bone marrow [ 53 , 54 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cimetidine was shown to be effective against the clastogenic effects of γ-rays [ 6 , 7 ] and X-rays [ 8 ] in vitro. It was also demonstrated to be protective against γ-rays and neutrons in vivo [ 7 , 9 – 12 ]. Cimetidine was shown to inhibit the activity of suppressor T cells [ 13 ] and was used in radioprotection to help the recovery of the lymphohematopoietic system effectively [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This supports the hypothesis that cimetidine may afford efficient protection against ionizing radiation or diseases that are characterized by in vivo free radical-mediated oxidative stress mechanisms [ 15 ]. It was shown that cimetidine, ranitidine, and famotidine produced a DRF of 1.5 to 2 against γ-ray-induced micronuclei in mouse bone marrow erythrocytes [ 9 , 16 ]. Cimetidine, compared with famotidine, was found to be more protective against mortality induced by radiation in mice [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A similar decrease in MnPCE induced by -irradiation has been described by other antioxidants such as amifostine, glutathione and cimetidine. 19,20 Treatment of mice with captopril at dose of 10 mg/kg before exposure to 2 Gy radiation reduced the frequency of MnPCE almost 2.18 fold. Among radioprotective agents, amifostine has been evaluated as a powerful radioprotector, but this drug is effective only at high doses which are close to the toxic level (i.e.…”
Section: Discussionmentioning
confidence: 99%